Cinematic cultures of descent: the other sides of the mountaineering story. Issue 1 (2nd January 2023) - Müller, Eva-Maria
ABSTRACT: This essay introduces the descent as a critical vantage point that broadens the mountain film genre and reconsiders modernist debates with an eye towards cinema's socio-ecological substance. I analyze three films—Philipp Stölzl's Nordwand (2008), Nils Gaup's Ofelaš (1987), and Jeff Orlowski's Chasing Ice (2012)—for how they highlight social connectivity and environmental sustainability in their accounts of national tragedy, Indigenous legend, and eco-catastrophe. Central to this inquiry are the multiperspectival and self-reflective qualities of cinema and the ways in which its immersive qualities dovetail into cinematic world-building and global decolonization. By bringing media ecology together with postcolonial scholarship on alpinist control and film historical reflections on descent, I argue that cinematic cultures of descent reveal the hidden stakes of alpinism and challenge established ideas of the perception of self and Other in modern mountaineering. This, in turn, prompts fresh registers of thinking mountains and mountaineering in ways that invite cultural renegotiations of gender roles, power, and individualism among mountaineers. Ultimately, it highlights the special role film plays in facilitating a change of perspective, thus affecting behavior in the human and non-human world.